A Misdiagnosed Case of Hypertrophic Gastropathy - Sushma Thapa; Arnab Ghosh; Gita Pun; Dilasma Ghartimagar; O. P. Talwar (Case Reports in Pathology)
Hypertrophic gastropathy is a rare idiopathic hyperproliferative disorder which may present as Menetrier’s disease (MD) characterized by foveolar hyperplasia in the gastric fundus and body. It is often accompanied by a severe loss of plasma proteins (including albumin) from the altered gastric mucosa. The disease occurs in two forms, a childhood form due to cytomegalovirus infection and an adult form attributed to overexpression of transforming growth factor-alpha (TGF-α). The most common symptoms include epigastric pain with fullness and vomiting and generalized peripheral edema with hypoalbuminemia. We present a case of 75-year-old female presenting with epigastric pain and vomiting. Upper gastrointestinal endoscopy and computed tomography scan revealed an irregular mucosal fold at the body and antrum and thickening of the stomach wall, respectively. Though the endoscopic gastric mucosal biopsy was nonspecific, the patient underwent partial gastrectomy due to clinicoradiological suspicion of carcinoma. On histopathology, the case was reported as hypertrophic gastropathy, consistent with MD. Though there is a strong clinical and radiological suspicion of malignancy in the hypertrophied gastric mucosa, MD should be one of the important differential diagnoses.